THE ROLE OF EMPOWERMENT SELF-REGULATION - Павленко, Ганна Володимирівна (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2017)
The publication focuses on the problems of individual empowerment and self-regulation. Is emphasized the special role of self-regulation in the process of empowerment. Empowerment in a general sense is a way of acquiring innerstrength, capabilities, reproduction of own sense of efﬁ ciency. Self-regulation refers to a conscious process of human mental activity of building, support and management of arbitrary activity aimed at achieving the objectives. There is marked the necessity for further theoretical and experimental studies of the concept of empowerment.